Library cafe as a service innovation a case study on Tweedle Book Café as a third place - Gali, Frances Andriette G.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
This case study was conducted focused on the promotion of library cafés, provision of services, policies in the usage of materials, perception of customers, and the difficulties that a library café establishment may encounter. To support the research, the Tweedle Book Café was used as the main café for the case study. Survey questionnaire and interview were used as instruments in the case study. A number of ocular visits and observations, along with the studies and literature related to the study were also used in supporting the study. 30 Tweedle Book Café users and the owner of the café were the main respondents of the case study. The results of the case study show that the Tweedle Book Café is an effective type of library café only receiving a minimal issue that can be settled along with the decision of the owner. This case study shows that innovation can contribute to the development of a library café and it is important of cater and satisfy the needs of the users because although the idea of library cafés is still new in the Philippines, their patrons make use of the space that they provide in a positive manner.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Tweedle Book Café; Library food and beverage policies